Stjørdalselva - Bjorvand, Harald (NAMN OG NEMNE, 2020)
The river which today bears the name Stjørdalselva is approximately sixty kilometres long and has its course through the municipalities of Meråker and Stjørdal. It ends in Trondheimsfjorden not far from Trondheim airport, Værnes. The last twenty kilometres it flows slowly through a flat, agricultural landscape, and the riverbed is accordingly characterised by a number of quite large meanders. For this reason the river was here called PrScand. *WarÅ f. > ONorse *Vara, an Ån-stem originally simply meaning ’(running) water’ which was later specialized to designate a slow-flowing and meandering river. The name of this part of the river is still preserved in the old farm name Værnes. It is also found in several other river, farm and parish names in Norway, e.g. Varåa, Varlo and Vardal. The upper part of the river from the confluence of the rivers Dalåa and Torsbjørka in Meråker to the Ingstad farms in Stjørdal about forty kilometres downstream has a much faster course through an extended valley. Several parts of the riverbed are here also quite straight, and this applies perhaps especially to the last two kilometres from the farm Sørkil to the Ingstad farms. A straight riverbed like this may be compared to a log, beam etc., and an old word with this meaning is in all probability found in the farm name Skjør (ONorse dat. j Stiore) in Eidsberg. This otherwise unknown noun ONorse *stjór n. or *stjórr m. ’log, beam etc.’ is here used metaphorically to designate a long tapering ridge which ends in a small promontory into the river Glomma. The farm Skjør being situated on the ridge is thus named after this location. The above mentioned straight stretch of Stjørdalselva may thus have had the name ONorse *Stjór f. which later became the name of the whole river, documeted in the compound ONorse Stjóra(r)dalr > Stjørdal(en).